A construção de sentidos-e-significados no HTPC: uma discussão sobre a questão da formação docente - Rocha, Eva Pereira da (2012)
This research, inserted into Contemporary Applied Linguistics (Moita Lopes, 2006), aims to critically understand the senses-and-meanings built in the meetings for teacher education (HTPC) in a school located in Alto Tietê in São Paulo. This is a critical interpretive research (Triviños, 2008) inserted in the critical paradigm. This study is underpinned by Vygotskian reference of the Socio-Cultural-Historical Theory and the enunciative-discursive approach of Bakhtin/Voloshinov (1985) and Bakhtin (1975/1998, 1992/2003) and the Circle. This research is in consonance with the studies produced in the Group of Inclusion in Linguistics Scenarios of Educational Activities GP-ILCA, which excel in questioning the language used and produced in the school context, as well as in promoting discursive practices as instruments of social transformation. Thus, the goal of this study is to contribute to the current discussion of teacher education, especially in state schools. The question that guides this work and intends to be answered in the analysis is What are the senses-and-meanings built by participants in the discussions in the meetings for teacher education - HTPC? The collection of data was performed by video and audio recordings of 4 HTPC meetings in 2010. The data was interpreted and analyzed by the categories of analysis: lexical choices and units of implication from the framework of Bronckart (1997/1999). The results showed that i) the focus of work in the HTPC meeting is to prepare the student for the assessment of SARESP and not on the issues of teaching and learning, ii) the HTPC is characterized as a space of transmission and imposition and the teacher formation is relegated to a second plan iii) the exemption and transference of the pedagogical work prevail, iv) the teachers disclaims the responsibility for the indiscipline and students teaching-learning problems and v) in the HTPC meetings, several issues are discussed and, consequently, there is no room for teacher formation